2017
DOI: 10.1007/s11482-017-9567-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Contextual Factors of Happiness and Life Satisfaction in a Low Middle Income Country

Abstract: Understanding individual and contextual factors of happiness and life satisfaction in a lowand middle-income country setting are important in the study of subjective well-being. This study aims to examine individual and contextual factors of happiness and life satisfaction in one of the happiest countries in the world: Indonesia. Data comes from the Indonesian Family Life Survey 2014 (N individual = 31,403; N household = 15,160; N district = 297). Results from a three-level ordered logit model show that factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 47 publications
4
30
0
6
Order By: Relevance
“…Further, the findings have revealed that males are less satisfied than females. This confirms the one carried out by Sujarwoto et al (2017), which has found that men are less satisfied than women. It is also the same direction as Graham & Soumya's (2012) study which discovered that generally those females are satisfied compared to males in the world.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Further, the findings have revealed that males are less satisfied than females. This confirms the one carried out by Sujarwoto et al (2017), which has found that men are less satisfied than women. It is also the same direction as Graham & Soumya's (2012) study which discovered that generally those females are satisfied compared to males in the world.…”
Section: Discussionsupporting
confidence: 91%
“…This has been emphasized by (Deneve, 1999;Diener et al, 1999;Veenhoven, 2016)'s studies which revealed that extraverted people are less depressed, and they express more their thankfulness than neurotic people. Finally, the findings of the current research replicate the one carried out by Sujarwoto et al (2017), which have shown that extraversion personality trait is significantly connected to life satisfaction and happiness. In sum, it is to say that extraversion personality traits, especially is greater correlates with both happiness and life satisfaction, which means that it affects people's way of reacting towards events that happen to their daily life.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Ancak bu pozitif duygular rastgele değildir ve mutluluk pozitif duyguların deneyimlenmesi ile başarı kazanır (12). Mutluluk ile ilgili yapılan araştırmalar incelendiğinde bu kavramın alanyazında yaşam doyumu (13,14), yalnızlık (15), şemalar (16,17) ve depresyon (18) gibi birçok kavramla çalışıldığı görülmektedir.…”
Section: Introductionunclassified